Math misconceptions: Mistakes, misunderstanding, and confusion - Kurudirek, Abdullah; Karim, Bnar; Sarhang, Delan; Tulqin , Safarov (ARKA INSTITUTE, 2025)
In this study, we investigate mathematical misconceptions, particularly prevalent among high school students, and offer solutions. The primary aims of our research include identifying the most common mathematical misconceptions, uncovering their underlying causes, and evaluating research-based solutions that have successfully addressed these issues. For this study, data were collected using a mixed-methods approach in Stirling Schools operating throughout Iraq. Data were gathered via a diagnostic test, as well as teacher interviews and classroom observations. The test revealed conceptual, procedural, and application problems, while interviews and observations gave qualitative information about the sources of misunderstandings and teaching tactics. The data analysis blended quantitative mistake classification with qualitative theme analysis to provide a complete picture of misunderstandings and effective training approaches. In light of the data obtained, we can state that misconceptions typically stem from a lack of conceptual understanding, over-reliance on procedural methods, and contextual misunderstandings. Additionally, it has been shown that conceptual education, visual aids, and peer-supported learning help eliminate mathematical misconceptions. These valuable findings hold significant implications for educators seeking to improve students' mathematical knowledge by emphasizing the importance of concept-based learning and providing opportunities for re-education. Through this study, we offer key insights into how widespread mathematical misconceptions can be effectively addressed, contributing meaningfully to mathematics education.